2013
DOI: 10.1194/jlr.m031476
|View full text |Cite
|
Sign up to set email alerts
|

Dietary xenosterols lead to infertility and loss of abdominal adipose tissue in sterolin-deficient mice

Abstract: Journal of Lipid Research Volume 54, 2013397 noncholesterol sterols. These noncholesterol sterols are primarily plant sterols, and the mammalian body prevents the retention of these noncholesterol sterols, only allowing cholesterol to be retained and metabolized by the body. The molecular mechanism(s) by which this occurs was elucidated by studies of the rare genetic disorder sitosterolemia (MIM #210250), which led to the identifi cation of two ABC "half-transporters" that are key to keeping these molecules ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…14,18 As shown in Figure 1A-B, Abcg8 Figure 1C) typically associated with human sitosterolemia. 11 These hematologic parameters were nearly identical in Abcg5-deficient mice fed an HS diet (not shown).…”
Section: Study Approvalmentioning
confidence: 90%
See 2 more Smart Citations
“…14,18 As shown in Figure 1A-B, Abcg8 Figure 1C) typically associated with human sitosterolemia. 11 These hematologic parameters were nearly identical in Abcg5-deficient mice fed an HS diet (not shown).…”
Section: Study Approvalmentioning
confidence: 90%
“…Abcg5-and Abcg8-deficient mice on a C57BL/6J background have been described previously 13,17,18 and have been deposited with Jackson Laboratories. GPIba-null mice 19 were generously provided by Dr. Jerry Ware (University of Arkansas).…”
Section: Mice and Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eluates were concentrated under 100% nitrogen, derivatized using a 99:1 solution of N,O-bis(trimethylsilyl) trifluoroacetamide (BSTFA/TMCS) and trimethylchlorosilane (TMCS), and dried under 100% nitrogen. Samples were resuspended in ethyl acetate and analyzed using gas chromatography-mass spectroscopy (GC-MS; Thermo Finnigan DSQ; Thermo Fisher Scientific, Madison, WI) using the conditions described previously (34). 25HC had an m/z of 131.0 with a retention time of 6.26 min, and 24-RS-HC had an m/z of 413.0 and a retention time of 17.80 min; these values were comparable to those reported previously (35).…”
Section: Animals and Primary Cell Cultures C57bl/6j (Bl6) Irf-1mentioning
confidence: 99%
“…In addition, PS has been reported to decrease serum estrogen levels in animals and disturb estrogen metabolism, which suggests an indication for reduced fertility (74, 75). PS are proposed to be responsible for modifying fat storage and fertility in ABCG5/G8 knockout mice via disruption of endocrine systems and mammalian physiology; although this claim has not been demonstrated in human subjects (76, 77). Research has shown that exclusion of PS from the diet and blocking dietary sterol absorption with ezetimibe treatment reversed infertility in ABCG5/G8 knockout mice (77).…”
Section: Trends In Sitosterolemia and Other Risk Factorsmentioning
confidence: 99%